Proceedings of the 16th Koli Calling International Conference on Computing Education Research 2016
DOI: 10.1145/2999541.2999549
|View full text |Cite
|
Sign up to set email alerts
|

Pauses and spacing in learning to program

Abstract: Conventional wisdom holds that time is an integral part of the learning process. Spacing out learning over multiple study sessions seems to be better for learning than having a single longer study session. Learners should also take pauses from the learning process to absorb, assimilate, and analyze what they have just learned. At the same time, pausing too often can be harmful for learning. Participants of two subsequent introductory programming courses completed programming tasks in an integrated development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Our belief is that this is partially due to focusing on too coarse grained data -it is likely that different students spend different proportions of time in different learning environments and material locations. Thus, effort should not be estimated solely based on the total study time, as even small pauses can account for large variations in learning outcomes [21]. Moreover, it is also important to know what the time is spent on -for example, knowledge on which material paragraphs the students spend their time on could provide additional insights on the students' struggles [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our belief is that this is partially due to focusing on too coarse grained data -it is likely that different students spend different proportions of time in different learning environments and material locations. Thus, effort should not be estimated solely based on the total study time, as even small pauses can account for large variations in learning outcomes [21]. Moreover, it is also important to know what the time is spent on -for example, knowledge on which material paragraphs the students spend their time on could provide additional insights on the students' struggles [22].…”
Section: Discussionmentioning
confidence: 99%
“…Factors affecting students' performance in programming courses have traditionally been studied with the purpose of being able to predict the students' performance. In this line of research, a myriad of predictors ranging from students' affective states [31], students' programming behavior [8,10,12,13,21,27,38] to complex programming process based metrics [5,20,30] have been constructed.…”
Section: Factors Affecting Performance In Programming Coursesmentioning
confidence: 99%
“…They also found that students who spaced more provided more constructive feedback to others and were more likely to answer correctly on their first attempt [50]. In contrast, Leppänen et al [28] found that students who spaced their practice of programming tasks achieved lower grades than those who did not. Interestingly, they show that short pauses (one to two seconds) while performing programming tasks correlated with higher exam grades, while longer pauses (ten seconds to five minutes) correlated with lower exam grades [28].…”
Section: Spacing Effect In Cs Educationmentioning
confidence: 96%
“…Interestingly, they show that short pauses (one to two seconds) while performing programming tasks correlated with higher exam grades, while longer pauses (ten seconds to five minutes) correlated with lower exam grades [28]. They also collected data from a survey to analyze students' perceptions of their studying and found that their reported self-regulation did not correlate with their spacing habits [28].…”
Section: Spacing Effect In Cs Educationmentioning
confidence: 99%
“…Other studies have identified a multitude of other predictors. Leppänen et al [26] found correlations between the types of pauses students take from writing program code and exam scores in a CS1 course. Leinonen et al [25] were able to predict student learning outcomes based on the key press latencies in their typing.…”
Section: Related Workmentioning
confidence: 99%